Financial intermediaries, markets and growth - Falko Fecht; Kevin Huang; Antoine Martin (Deutsche Bundesbank, 2005)
We build a model in which financial intermediaries provide insurance to households against a liquidity shock. Households can also invest directly on a financial market if they pay a cost. In equilibrium, the ability of intermediaries to share risk is constrained by the market. This can be beneficial because intermediaries invest less in the productive technology when they provide more risk-sharing. Our model predicts that bank-oriented economies should grow slower than more market-oriented economies, which is consistent with some recent empirical evidence. We show that the mix of intermediaries and market that maximizes welfare under a given level of financial development depends on economic fundamentals. We also show the optimal mix of two structurally very similar economies can be very different.
Keywords: E44; G20; G10; 330; Financial Intermediaries; Risk Sharing; Finance and Growth; Comparing Financial Systems; Finanzintermediär; Finanzmarkt; Investition; Allokation; Wirtschaftswachstum; Overlapping Generations